Implementasi Mesh Wi-Fi untuk Mengatasi Deadzone di Rumah - Andi Muhammad Nur Hidayat; Muhammad Ryaas Rahmat; Andi Nur Rizqah Aulia Renggala (Subaltren Inti Media, 2026)
including within household environments. However, the presence of areas without signal coverage, or dead zones, remains a serious obstacle in the use of conventional router-based wireless networks. This study aims to evaluate the effectiveness of implementing a Mesh Wi-Fi network in addressing dead zone issues in residential settings, taking into account room configuration, wall obstructions, and potential interference. The research was conducted using an experimental approach by deploying Wi-Fi 6–based Mesh Wi-Fi devices in a two-story house that previously experienced connectivity issues. Data were collected through measurements of signal strength, download and upload speeds, latency, and network stability across three critical areas of the house. The results show a significant improvement, with an average increase of 26.05 dBm in signal strength and more than a 500 percent increase in download speeds after the implementation of Mesh Wi-Fi compared to a single-router network. In addition,the variation in signal quality across locations decreased, indicating a more even distribution of network coverage. These findings demonstrate that Mesh Wi-Fi is an effective and practical solution for improving network quality in homes with complex building structures, and it is capable of overcoming the limitations of traditional solutions such as signal boosters or additional routers. Therefore, the implementation of Mesh Wi-Fi is recommended as an alternative for providing stable internet connectivity in modern households.